Pengembangan Wilayah Berdasarkan Komoditas Unggulan di Kecamatan Petang, Kabupaten Badung, Provinsi Bali - I PUTU SURYA PRATAMA; MADE ANTARA; IDA AYU LISTIA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Regional economic growth is essentially a series of businesses and policies aimed atimproving economic relations from the primary sector to the secondary and tertiarysectors. Economic development is a policy focused on improving people's livingstandards, expanding employment, declaring revenue sharing and improving regionalrelationships among regions. The balance of development in North Badung and SouthBadung is often a discourse. The synergy of the tourism and agriculture sectors is theanswer to making this happen. This study aimed to identify superior and non-superiorcommodities as well as formulate a strategy of developing superior commodities inPetang District. The data used were secondary data in the form of time series data oragricultural production data of Badung Regency and Petang District in 2011-2015. Thedata were collected by document study and in-depth interviews, analyzed by LocationQuotient (LQ) and SWOT analysis method. The result of the analysis shows that foodcommodities belonging to the main commodities are corn, peanut, sweet potato, cassavaand asparagus while the rice commodity is included in non-commodity commodity.Plantation commodities included in the main commodities are coffee, cloves andvanilla, while coconut and cocoa are included in non-commodity commodities. Strategicdevelopment of superior commodities that need to be taken is to explore the potential ofnatural resources and improve the quality of human resources for the development ofsuperior commodities in Petang District.